Squamous Cell Carcinoma Differentiation of Ovarian Mature Cystic Teratoma in a Postmenopausal Woman Presented As Acute Abdomen - Cihan Kaya; Hüseyin Cengiz; Murat Ekin; Levent Yaşar; Nurten Sever (Medical Network, 2012)
To emphasis that, although it is rare, the mature cystic teratomas can transform to malignancy and can be cause of acute abdomen. A 61 year old postmenopausal woman who had been operated because of acute abdomen and adnexal mass and the pathologic result was reported as squamous cell carcinoma differentiated from mature cystic teratoma. It has to be keep in mind, due to the compounds of mature cystic teratomas, they are tend to torsion, can be cause of acute abdomen and rarely, malignant differentiation can be seen.